2002
DOI: 10.1002/1616-3028(20020517)12:5<367::aid-adfm367>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Nematic Polymer Mixture Containing Crosslinker and Photosensitive Chiral Dopant: New Type of Materials with Tunable Photo-Optical Properties

Abstract: A cholesteric mixture based on a menthyl‐containing copolymer, photosensitive chiral dopant, mesogenic diacrylate, and photoinitiating agent has been prepared. The mixture shows a selective light reflection in the visible light spectral region. The action of UV irradiation (313 or 365 nm) on the planar‐oriented films generates the occurrence of two parallel processes: E/Z (i.e., cis–trans) photoisomerization of the chiral dopant and photopolymerization of the diacrylate. The first process leads to the untwisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Recently, a polymeric LC system was reported where switching an azobenzene dopant was accompanied by crosslinking of the polymeric LC due to the presence of a diacrylate and a polymerization initiator. [19] This resulted in simultaneous switching and crosslinking from a polymeric LC state showing an approximately 645 nm reflection, to a crosslinked state maximally showing an approximately 750 nm reflection. In an approach comparable to our approach reported in this article, the authors make elegant use of the simultaneously occurring light-induced switching and crosslinking, but only red colored liquid-crystalline and crosslinked samples were obtained.…”
Section: Introductionmentioning
confidence: 41%
“…Recently, a polymeric LC system was reported where switching an azobenzene dopant was accompanied by crosslinking of the polymeric LC due to the presence of a diacrylate and a polymerization initiator. [19] This resulted in simultaneous switching and crosslinking from a polymeric LC state showing an approximately 645 nm reflection, to a crosslinked state maximally showing an approximately 750 nm reflection. In an approach comparable to our approach reported in this article, the authors make elegant use of the simultaneously occurring light-induced switching and crosslinking, but only red colored liquid-crystalline and crosslinked samples were obtained.…”
Section: Introductionmentioning
confidence: 41%
“…[3,4] The sensitivity of ChLCs to external parameters, such as temperature, the presence of impurities, and light, has led to many practical applications and has been the subject of much theoretical research. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several mechanisms have been proposed to explain the role that the dopant molecules play in the modulation of the macroscopic chirality of ChLCs. [11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases.…”
Section: Introductionmentioning
confidence: 46%
“…Among these, the change in the helical pitch caused by photochemical reactions in the Ch-LCs is especially of interest [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Azobenzene is a typical photochromic compound, which changes its molecular shape upon photoirradiation.…”
Section: Introductionmentioning
confidence: 46%